Effects of Kimchi on human health: A protocol of systematic review of controlled clinical trials. Issue 13 (March 2018) - Kim, Myung-Sunny; Yang, Hye Jeong; Kim, Soon-Hee; Lee, Hye Won; Lee, Myeong Soo
Abstract: Background: Kimchi, a traditional, fermented Korean food that is consumed daily, has been recognized as a health food due to its beneficial effects on human health. The aim of this overview is to critically evaluate all clinical trials of the use of Kimchi in the treatment of any condition or symptom. Methods and analysis: Eight databases will be searched from inception until March 2018. We will include all prospective trials, including randomized controlled trials (RCTs), non-RCTs, and uncontrolled trials. The methodological quality of the trials will be assessed using Cochrane risk of bias (ROB) assessment tool and ROB in nonrandomized studies-I for RCTs and non-RCTs, respectively. Ethics and dissemination: Ethical approval will not be required, given that this protocol is for a systematic review. The full systematic review will be published in a peer-reviewed journal. The review will also be disseminated electronically and in print. Updates of the review will be conducted to inform and guide health care practice and policy. Trial registration number: PROSPERO 2018 CRD42018087375